Peningkatan Self Regulation Learning melalui Layanan Bimbingan Belajar Daring Model STAD Berbantuan Media Thinglink - Malthelda Yulianti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2022)
This study aims to improve students' self-regulation learning through online tutoring services with the Student Teams Achievement Divisions (STAD) model assisted by media thinglink. The research subjects were students of class XI MIPA-1 SMA Negeri 2 Yogyakarta in the 2020/2021 academic year. The type of research carried out is Action Research for Counseling Classes (PTK BK) which follows the model of Stephen Kemmis and Robin McTaggart, through the stages of planning, acting, observing, and reflecting. The research method is observation using an instrument prepared by the researcher with reference to the study of the theory used. The data analysis technique uses a qualitative descriptive technique, which describes the implementation of online tutoring services with the STADmodel assisted by media thinglink from the planning, action implementation, observation and reflection stages in each cycle. The results showed that there was an increase in students' self-regulation learning abilities, in the metacognitive aspect before the action was in the position of 77.20%, after the second cycle of action became 89.90% increased by 12.70%. In the aspect of motivation before the action, 76.70% after the second cycle of action increased to 87.40%, the increase in the motivational aspect was 10.70%. Furthermore, in the behavioral aspect before the action was taken, 74% after the second cycle of action became 83.30%. Improved indicators on behavioral aspects increased by 9.30%. From the results of this counseling class action research, it can be concluded that the online tutoring service model of the STAD assisted by media thinglink can improve the self-regulation learning of students in class XI MIPA-1 SMA Negeri 2 Yogyakarta.